2005
DOI: 10.1021/np050013w
|View full text |Cite
|
Sign up to set email alerts
|

Koniamborine, the First Pyrano[3,2-b]indole Alkaloid and Other Secondary Metabolites from Boronella koniambiensis

Abstract: Two new alkaloids, (-)-cis-1,2-dihydroxy-1,2-dihydromedicosmine (3) and koniamborine (4), have been isolated from Boronella koniambiensis aerial parts. Their structures have been established from NMR and mass data. Koniamborine is a novel type of alkaloid, which derives from the pyrano[3,2-b]indole basic skeleton, described for the first time from nature. 6-Methoxy-1-methylisatin, also present in the plant material, can be considered biogenetically as a degradation product of the fused pyrone ring of 4.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
19
0

Year Published

2007
2007
2023
2023

Publication Types

Select...
9
1

Relationship

0
10

Authors

Journals

citations
Cited by 42 publications
(19 citation statements)
references
References 21 publications
0
19
0
Order By: Relevance
“…) has a fused 2,2‐dimethyl‐2 H ‐pyran ring rather than the simple methoxy group found in 49 . It was isolated from the aerial parts of Boronella koniambiensis and was slightly cytotoxic against the murine L1210 leukemia cell line (IC 50 48.0 μM) …”
Section: Bioactivities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
“…) has a fused 2,2‐dimethyl‐2 H ‐pyran ring rather than the simple methoxy group found in 49 . It was isolated from the aerial parts of Boronella koniambiensis and was slightly cytotoxic against the murine L1210 leukemia cell line (IC 50 48.0 μM) …”
Section: Bioactivities Of Quinoline and Quinazoline Alkaloidsmentioning
confidence: 99%
“…1,4‐Benzothiazines are a set of biologically active heterocyclic molecules . Tandon et al reported the synthesis of benzothiazines in ionic liquids.…”
Section: Miscellaneousmentioning
confidence: 99%
“…Carbazole, and especially heterocycle-containing carbazole derivatives, are embodied in many naturally occurring products [13] and display a broad spectrum of useful biological activities such as antitumor, antimitotic, and antioxidative activities [46]. They are also widely used as building blocks for new organic materials [710], and play a very important role in electroactive and photoactive devices [1114].…”
Section: Introductionmentioning
confidence: 99%